VRP variants applicable to collecting donations and similar problems: A taxonomic review. (February 2022) - Gutiérrez-Sánchez, Alexander; Rocha-Medina, Linda Bibiana
Highlights: Few VRP models found to collecting donations about reverse logistics and similar. CVRP applied to collect donations to solve the proposed model named Donation Collection Problem (DCP). Based on Closer Insertion, Sweep Method, and Genetic Algorithm, a hyperheuristic can be proposed to solve de DCP. The proposed model has other assumptions that cannot be taking into account before. Abstract: This paper presents a taxonomic review of Vehicle Routing Problem (VRP) with Time Windows (VRPTW), Pick-up and Delivery Problem (PDP), and Periodic Vehicle Routing Problem (PVRP). We focus on the problems of collection goods and similar. The applications of these models are typical like found in the literature; however, not applications specifically about collecting donations were found. Because of concern for the environment, social equity, and business efficiency, specific research fields related to green and reverse logistics have arisen; thus, optimization of waste (second-hand goods, food, recyclable/no recyclable waste, etc.) collection routes gain interest. In the literature reviewed, we found several VRP models of goods collection applied to picks-up of returned items, End-of-Life (EOL) products, Municipal Solid Waste collection (MSW), and Waste Collection Problem (WCP). The primary purpose of this paper is to structure the taxonomy of VRPTW, PDP and PVRP problems applicable to collecting donations according to its features, solution methods, and mathematical formulation. Likewise, provide the reader with an outline orderly and differentiated from the VRP models associated with pick up items and delivery orders (VRPPD), backhauling customers (VRPB), collection waste, and similar problems to propose our problem. For clarity, Appendix A includes the acronym used in these types of problems. This paper is part of a larger research project called "CVRPTW model applied to collecting food donations, " intending to contribute to a new perspective on the routing problems little explored.